Organic Nonvolatile Resistive Switching Memory Based on Molecularly Entrapped Fullerene Derivative within a Diblock Copolymer Nanostructure - Jo, Hanju; Ko, Jieun; Lim, Jung Ah; Chang, Hye Jung; Kim, Youn Sang (WILEY-V C H VERLAG GMBH, 2013)
Organic nonvolatile resistive switching memory is developed via selective incorporation of fullerene derivatives, [6,6]-phenyl-C61 butyric acid methyl ester (PCBM), into the nanostructure of self-assembled poly(styrene-b-methyl methacrylate) (PS10-b-PMMA130) diblock copolymer. PS10-b-PMMA130 diblock copolymer provides a spatially ordered nanotemplate with a 10-nm PS nanosphere domain surrounded by a PMMA matrix. Spin casting of the blend solution of PS10-b-PMMA130 and PCBM spontaneously forms smooth films without PCBM aggregation in which PCBM molecules are incorporated within a PS nanosphere domain of PS10-b-PMMA130 nanostructure by preferential intermixing propensity of PCBM and PS. Based on the well-defined PS10-b-PMMA130/PCBM nanostructure, resistive random access memory (ReRAM) exhibits significantly improved bipolar-switching behavior with stable and reproducible properties at low operating voltages (RESET at 1.3 V and SET at 1.5 V) under ambient conditions. Finally, flexible memory devices are achieved using a nanostructured PS10-b-PMMA130/PCBM composite in which no significant degradation of electrical properties is observed before and after bending.
Keywords: DEVICE APPLICATIONS; FLEXIBLE SUBSTRATE; THIN-FILM; POLYMER; ELECTRONICS; TRANSISTORS; MECHANISMS; TRANSPORT; LAYER; OXIDE